Proceedings of the 31st IEEE/ACM International Conference on Automated Software Engineering 2016
DOI: 10.1145/2970276.2970353
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on dependence clusters for effort-aware fault-proneness prediction

Abstract: A dependence cluster is a set of mutually inter-dependent program elements. Prior studies have found that large dependence clusters are prevalent in software systems. It has been suggested that dependence clusters have potentially harmful effects on software quality. However, little empirical evidence has been provided to support this claim. The study presented in this paper investigates the relationship between dependence clusters and software quality at the functionlevel with a focus on effort-aware fault-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 41 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…More recently we were able to demonstrate the potentially pernicious effects of dependence clusters [135], thereby motivating this initial interest. As a result of chasing an unexpected use-case for a deployed research prototype, we were thus rewarded with a rich seam of novel research questions and intellectually-stimulating scientific investigation.…”
Section: B Serendipitous Deployment Pivotsmentioning
confidence: 88%
“…More recently we were able to demonstrate the potentially pernicious effects of dependence clusters [135], thereby motivating this initial interest. As a result of chasing an unexpected use-case for a deployed research prototype, we were thus rewarded with a rich seam of novel research questions and intellectually-stimulating scientific investigation.…”
Section: B Serendipitous Deployment Pivotsmentioning
confidence: 88%
“…To study the relationships between dependence clusters and defect‐proneness in effort‐aware defect prediction, Yang et al [124] empirically evaluated the effect of dependence clusters with different statistical techniques. They found that large dependence clusters, functions inside dependence clusters tend to be more defect‐prone, which help us to better understand dependence clusters and its effect on software quality in the effort‐aware context.…”
Section: Effort‐aware Context‐based Defect Prediction Studiesmentioning
confidence: 99%
“…In this situation, a cost-effective model would rank the files in descending order of their bug density. The effort-aware ranking effectiveness of classification techniques in defect prediction is always evaluated by cost-effectiveness (CE) curve, which is widely used in prior works [29], [44], [63]. Figure 5 shows an example of the CE curve.…”
Section: E Evaluationmentioning
confidence: 99%
“…The preliminary step of bug fixing is to identify the potential locations of bugs in a software project. In the last decades, many software defect prediction models [16], [17], [22], [26], [54], [55], [63], [65] have been proposed to identify defect-prone modules, which could help software engineers test and debug software more effectively and efficiently. In order to achieve accurate defect prediction, it is essential to use quality defect predictors and modeling techniques to build the prediction models.…”
Section: Introductionmentioning
confidence: 99%